Trade war and grain import resilience: evidence from China’s response to U.S. Tariffs - Han, Dong; Wu, Yuhui; Si-Si, Chen (Frontiers in Sustainable Food Systems, 2025)
Examing the impact of China-US trade friction on China’s grain import resilience can provide valuable insights for China and other developing countries in achieving food security. On the basis of defining the theoretical connotation of China’s grain import resilience, this study employs data from 2013 to 2023 and applies a difference-in-differences (DID) approach to quantitatively analyzes the impact of China US trade frictions on China’s grain import resilience. The study shows that the trade friction between China and the United States has an obvious negative impact on the resilience of China’s grain imports. During the U.S.-China trade friction period, China’s grain import prices rose, price volatility increased, import volume declined, import tempo changed, and the degree of import diversification declined. This shows that China’s grain import resilience, recovery capacity and transformation and upgrading capacity need to be improved. Developing countries can enhance their food supply capacity by adopting measures such as diversifying import sources, expanding domestic production, promoting regional cooperation, and establishing strategic reserve systems. Specific strategies may include actively cultivating new trade partnerships, strengthening irrigation and water conservancy infrastructure, and modernizing grain storage facilities.